Kassinopoulos, Marios - (:unkn) unknown (My University, 2026)
Marios Kassinopoulos is an Assistant Professor at the Department of Electrical Engineering and Information Technology. He first graduated from the University of Grenoble in France in the Electrical, Electronic and Control Engineering. Then he continued his studies at the University Paul Sabatier in Toulouse where he got his Ph.D in Control Engineering. He has done further studies at the University of Social Sciences in Toulouse and he is a holder of a Bachelor and a Master degree in Economics. He has worked for 3 years in the National Science Research Centre in France and then in the Higher Technical Institute in Cyprus. His research work is mainly related to Control Systems, Telemedicine and Engineering Education.